Panel containing three serum microRNAs: a promising biomarker for early detection of bladder cancer - Ge, Zhenjian; Lin, Shengjie; Lu, Chong; Xia, Yong; Li, Rongkang; Li, Xinji; Sun, Chen; Wen, Zhenyu; Chen, Wenkang; Li, Yingqi; Li, Mingyang; Lin, Yu; et al. (Frontiers in Oncology, 2024)
BackgroundBladder cancer (BC) is a common tumor worldwide. Screening for BC currently lacks a highly efficient, non-invasive, and inexpensive method. Serum microRNA (miRNA), which is stable and commonly present, has the potential to serve as a novel marker for BC diagnosis.Materials & methodsBased on a study involving 112 BC patients and 112 healthy subjects, we conducted this research in three phases to identify applicable microRNAs (miRNAs) in serum for BC diagnosis using quantitative reverse transcription polymerase chain reaction (qRT-PCR). A panel with optimal diagnostic value was developed. Additionally, we used bioinformatic analysis to explore the potential biological functions of the crucial miRNAs.ResultsThe diagnostic panel consisted of miR-212-3p, miR-30c-5p, and miR-206, with an area under the curve (AUC) of 0.838, sensitivity of 83.33%, and specificity of 73.81%. Furthermore, ATF3, GJA1, JPH2, MVB12B, RUNX1T1, SLC8A1, SPATA6, and TPM3 may be potential target genes of these three miRNAs.ConclusionWe developed a three-miRNA panel that could serve as a highly efficient and inexpensive biomarker for BC diagnosis and screening.